Evaluating the effects of European support measures for Italian organic farms. (March 2021) - Casolani, Nicola; Nissi, Eugenia; Giampaolo, Antonio; Liberatore, Lolita
Highlights: The European Union supports organic agriculture for its environmental advantages. Italian organic farming is supported through measure 11 of the Rural Development Program. The impact of organic support measures has been analyzed in Italian farms. Funds reveal a positive impact on the competitiveness of organic farms. Abstract: Today, a model for an eco-friendly agricultural sector represents a necessity. Organic agriculture is a production system that tries to reach this goal. European programs encourage farmers into being more environmentally conscious: the funds for organic agriculture support producers that from conventional convert to, or maintain, organic farming practices. This paper analyzes the impact of European funds allocated to organic farms under the 2014–2020 Rural Development Program. The first stage, consisted in determining a score corresponding to the efficiency of organic farms in Italian Provinces and Regions through the Data Envelopment Analysis, using economic variables as input and output. The second stage, regards the impact of regional funding towards organic agriculture which was determined in relation to farms' efficiency score with a Tobit regression. Measure 11 of the Rural Development Program and its relative sub-measures 11.1 (conversion from conventional farming to organic farming) and 11.2 (the maintenance of organic agriculture) strongly impact on organic farms' score. The evidence found supports the European strategy, confirming the usefulness of having these two distinct measures, and supports organic farms into starting and consolidating an organic business.